Euthanasia Through Cervical Dislocation or CO2 Might Affect Keel Bone Fracture Prevalence in 30-Week-Old Laying Hens - Rufener, Christina; Pullin, Allison N.; Blatchford, Richard A. (Frontiers in Animal Science, 2021)
Laying hens are susceptible to keel bone fractures due to continuous endogenous calcium resorption for eggshell formation. Although it is assumed that external trauma to the keel bone, e.g., due to collisions, is the main cause for fractures, accumulated forces or asymmetric load on a weakened bone might contribute to the high keel bone fracture prevalence found in commercial laying hens. The objective of this study was to investigate whether forces applied to the keel due to involuntary convulsions and uncontrolled wing flapping during euthanasia have the potential to cause keel bone fractures. Two hundred and seventy Dekalb White laying hens were euthanized at 30 weeks of age using cervical dislocation (n = 60) or CO2 (n = 210). All hens were radiographed immediately before and after euthanasia. Radiographs were compared side by side to detect new fractures. Four out of the 270 hens (1.5%) obtained a fracture during euthanasia. Specifically, 0.95% of hens euthanized with CO2 (2 out of 210) and 3.3% of hens euthanized through cervical dislocation (2 out of 60) obtained a euthanasia-induced fracture. All four hens with a euthanasia-induced fracture had signs of damage to the keel before euthanasia, indicating that pre-existing fractures could affect fracture susceptibility. Based on our results, we cannot rule out that convulsions during euthanasia can cause keel bone fractures in laying hens. In studies investigating keel bone integrity in birds euthanized with CO2 or cervical dislocation, fracture prevalence might be overestimated. Future research is needed to assess whether euthanasia might be more likely to cause keel bone fractures in older birds and to quantify the frequency and strength of convulsions as a potential cause of fractures.